Possible Gender Differences in Classical Music, Flamenco and Fado - Alicia Garcia-Falgueras (Neuroscience Insights)
Music is an art form and cultural activity whose language, the sounds and silences, is organized in time with logic and sensitivity. Music as a whole is the result of an ancestral nonverbal and international mode of human expression and communication. The primitive and former mother-child bonding might be highly influenced and modulated by the music and singing with their babies. Musicality and music imply two different sides of the same coin, where the former is based on the human capacity to produce the latter. Some theories about evolution suggest music might have an adaptive advantage for humans in society. Historical examples of different styles in music point out that if any allusion or reminder about gender in music might happen most probably occurs in folk non always written pagan or secular music with lyrics or voice. This genre of music usually tells about traditional gender differences in jobs, habits, lifestyles, etc., and has a clear preference for male musicians, while on the contrary, classical music usually does not have a clear gender difference in meaning, and instruments are played by both. In this text, I explore and empirically describe, neuroanatomically or functionally, some examples of different genres of music and brain differences, related to music and dance. Three different genres of music (Classical music, Fado and Flamenco) are explored in an attempt to elucidate some reasons for possible gender differences.